Evidence for genetic diversity in Trypanosoma (Nannomonas) congolense - Majiwa, Phelix A.O.; Hamers, R.; Meirvenne, N. van; Matthyssens, G. (Cambridge University Press, 1986)
Genetic proximity between two karyotypic groups of Trypanosoma congolense was investigated using as hybridization probes: (i) total genomic DNA, (ii) a 35 nucleotide long synthetic oligonucleotide, and (iii) non-variant antigen type (non-VAT) specific complementary DNAs. The phylogenetic relationship between Trypanosoma brucei and T. evansi, both of which are accepted species in the subgenus Trypanozoon, was used as a reference to assess the phylogenetic proximity of the two groups of T. congolense. Results indicate that some morphologically indistinguishable T. congolense populations differ in a variety of molecular and genetic properties: molecular karyotypes, majority of the DNA sequences, and the restriction enzyme sites in the genomic environments of various conserved genes. The implications of these findings for trypanosome evolution and T. congolense epidemiology are discussed.